2014
DOI: 10.1038/nmat4033
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of oscillatory behaviour of Pt nanoparticles catalysing CO oxidation

Abstract: Many catalytic reactions under fixed conditions exhibit oscillatory behaviour. The oscillations are often attributed to dynamic changes in the catalyst surface. So far, however, such relationships were difficult to determine for catalysts consisting of supported nanoparticles. Here, we employ a nanoreactor to study the oscillatory CO oxidation catalysed by Pt nanoparticles using time-resolved high-resolution transmission electron microscopy, mass spectrometry and calorimetry. The observations reveal that perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
424
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 383 publications
(442 citation statements)
references
References 40 publications
16
424
2
Order By: Relevance
“…The periodic switching between these states of low and high activity gives rise to the observed modulation of the reaction rate as it is observed in the oxidation of CO on Pt(110) under UHV conditions [1]. More recently, Vendelbo et al [54], using in situ time-resolved high-resolution transmission electron microscopy coupled with mass spectrometry, have shown that periodic changes in the oxidation of CO at atmospheric pressure are synchronous with a periodic faceting of Pt nanoparticles. It means that this so-called faceting mechanism can exist in a wide pressure range from UHV to elevated pressures.…”
Section: Discussionmentioning
confidence: 91%
“…The periodic switching between these states of low and high activity gives rise to the observed modulation of the reaction rate as it is observed in the oxidation of CO on Pt(110) under UHV conditions [1]. More recently, Vendelbo et al [54], using in situ time-resolved high-resolution transmission electron microscopy coupled with mass spectrometry, have shown that periodic changes in the oxidation of CO at atmospheric pressure are synchronous with a periodic faceting of Pt nanoparticles. It means that this so-called faceting mechanism can exist in a wide pressure range from UHV to elevated pressures.…”
Section: Discussionmentioning
confidence: 91%
“…Prominent examples in which TEM was used to gain insights into dynamic structure changes of catalysts are the restructurings of Cu surfaces of a Cu/ZnO catalyst in different gas atmospheres (see also Figures 5 and 6),46, 47 carbon nanofiber growth on a Ni catalyst during methane decomposition,14 and the refacetting of Pt nanocrystals during CO oxidation in a nanoreactor at 1 bar and at elevated temperatures 89…”
Section: Advancing the Characterization Methods: Following Dynamicsmentioning
confidence: 99%
“…However, surfaces of most materials tend to restructure in reactive gas environments and such changes have a profound feedback on catalysts' properties. It has therefore remained an important milestone in catalysis and surface sciences to functionalize electron microscopy for operando studies in which the catalyst surface structure and properties are simultaneously evaluated at the atomic-scale and under relevant reaction conditions.Here, we report on a nanoreactor system that enables combined electron microscopy and functional measurements of catalysts [2][3][4][5][6] and is available from Thermo Fisher Scientific. The nanoreactor is a micro-electro-mechanical system device integrating a 5-µm-high, one-pass and bypass-free gas-flow channel, a microheater and an array of 15-nm-thick electron-transparent windows of silicon nitride (Figure 1) [4].…”
mentioning
confidence: 99%
“…Moreover, mass spectrometry of gas exiting the reaction zone is made possible by the small reaction volume of ca. 0.3 nL and reaction calorimetry is accessed from the power compensation used for isothermal operation of the microheater [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation